Un féminisme décolonial - Vergès, Françoise (La fabrique, 2019)
Dans le débat public, être décolonial est une infamie. Dans les universités, dans les partis de gauche et d'extrême gauche, les syndicats, les associations féministes, partout on traque une "pensée décoloniale" infiltrée et funeste pour le vivre-ensemble. Dans ce livre, Françoise Vergès élucide l'objet du scandale. Le féminisme décolonial révèle les impensés de la bonne conscience blanche ; il se situe du point de vue des femmes racisées : celles qui, travailleuses domestiques, nettoient le monde ; il dénonce un capitalisme foncièrement racial et patriarcal. Ces pages incisives proposent un autre récit du féminisme et posent toutes les questions qui fâchent : quelles alliances avec les femmes blanches? Quelle solidarité avec les hommes racisés? Quelles sont les premières vies menacées par le capitalisme racial? Pourquoi les néofascismes s'attaquent-ils aux femmes racisées? Ce livre est une invitation à renouer avec la puissance utopique du féminisme, c'est-à-dire avec un imaginaire à même de porter une transformation radicale de la société.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; OFDIG; anticapitalisme; approches et analyses; com5170; cours; cycles supérieurs; europe; fem1000; fem7000; france; féminisme décolonial; har4600; incontournable; justice sociale; lit4700; pol4212; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; théories féministes

Sous le regard de l'Occident : recherche féministe et discours colonial - Mohanty, Chandra Talpade (Sexe, race, classe pour une épistémologue de la domination, 2009)
L’analyse de la construction intellectuelle et politique des « féminismes du tiers-monde » implique nécessairement deux mouvements simultanés : d’une part, une critique interne des féminismes « occidentaux » hégémoniques et, d’autre part, la formulation de problématiques et de stratégies féministes autonomes et ancrées géographiquement, historiquement, culturellement. Le premier mouvement consiste à déconstruire et décomposer ; le second, à concevoir et construire.
Keywords: approches et analyses; cours; discours dominant; droits des femmes*; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; incontournable; premier cycle; privilèges; systèmes d'oppressions; thématiques

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme